Antarctica - Rolston, Holmes, 1932-2025, author; Gale, publisher (Colorado State University. Libraries, 2009)
Antarctica, the seventh continent, is anomalous, compared with the six inhabited continents. The usual concerns of environmental ethics on other continents fail without sustainable development, or ecosystems for a "land ethic," or even familiar terrestrial fauna and flora. A political Antarctic regime developed policy with a deepening ethical sensitivity over the second half of the last century remarkably exemplified in the Protocol on Environmental Protection to the Antarctic Treaty (Madrid Protocol) at the end of the century, protecting "the intrinsic value of Antarctica," though puzzles remain about how to value Antarctica.
Keywords: value; environmental ethics; land ethic; values; Antarctica